Viruses of Microbes: the latest conquests - Oliveira, Ana (2022)
This book covers abstracrs from the most recent advances in ecology and evolution of microbial viruses, virus structures and function, virus-host interaction, agro-food, veterinary and environmental biotechnology applications and phage therapy.